2019
DOI: 10.1371/journal.pbio.3000054
|View full text |Cite
|
Sign up to set email alerts
|

The amplitude in periodic neural state trajectories underlies the tempo of rhythmic tapping

Abstract: Our motor commands can be exquisitely timed according to the demands of the environment, and the ability to generate rhythms of different tempos is a hallmark of musical cognition. Yet, the neuronal underpinnings behind rhythmic tapping remain elusive. Here, we found that the activity of hundreds of primate medial premotor cortices (MPCs; pre-supplementary motor area [preSMA] and supplementary motor area [SMA]) neurons show a strong periodic pattern that becomes evident when their responses are projected into … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
64
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 77 publications
9
64
0
2
Order By: Relevance
“…Neither approach is able to intrinsically account for biases in subjective duration by content because both are rooted in the idea that the brain attempts to track clock time. While tracking clock time is likely to be useful for short, repetitive motor commands such as drumming (11)(12)(13)(14) this is not necessarily the case for longer intervals, and indeed as established, subjective experience of longer intervals is characterized more by deviation from rather than adherence to clock time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither approach is able to intrinsically account for biases in subjective duration by content because both are rooted in the idea that the brain attempts to track clock time. While tracking clock time is likely to be useful for short, repetitive motor commands such as drumming (11)(12)(13)(14) this is not necessarily the case for longer intervals, and indeed as established, subjective experience of longer intervals is characterized more by deviation from rather than adherence to clock time.…”
Section: Introductionmentioning
confidence: 99%
“…Many animal and human electrophysiology and neuroimaging studies have searched for potential neural regions or putative mechanisms underlying time perception (15,16). This literature finds potential mechanisms in a diverse set of regions including pre-/supplementary motor areas (11,14,17), parietal areas (18,19), insula (20), midbrain dopaminergic neurons (21), and hippocampus and entorhinal cortex (22)(23)(24)(25). The diversity of neural regions apparently associated with human time perception supports the intuition underlying the population clock approach -that the dynamics of a neural system can be interpreted as reflecting time to an external observer because it is dynamic, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Our motivating hypothesis, derived from prior studies 7,11,[14][15][16][19][20][21][39][40][41] , is that SMA tracks internal and/or 74 contextual factors for the purpose of guiding action. If so, the SMA population response should be 75 shaped by the need to consistently distinguish situations that involve different future actions, even if the 76 current motor output is identical.…”
mentioning
confidence: 99%
“…It has also been found that there is tuning for interval and/or serial order as an orderly change in the power of transient modulations in β- and γ- bands across putaminal LFPs during the execution of the SCT (Bartolo et al, 2014). Recent research shows that the neural population trajectories during SCT in SMA/preSMA can act as a neural clock (Gámez et al, 2019). However, the neural code linked to the temporal production of this neural clock during SCT remains unknown.…”
Section: Introductionmentioning
confidence: 99%